Performance of Floor Reared White Leghorn Layer on Different Stocking Density and Feed Restriction Regimes - Singh, R.; Khanna, K.; Wadhwani, K.N.; Joshi, R.S.; Patel, A.M. (International Journal of Poultry Science, 2008)
Increase in feed prices in recent years has stimulated renewed interest in the area of feed restriction and simultaneously the birds have to provide space for feeding, watering and normal movements for their optimum growth and production. Thus, a great emphasis has been laid on feeding system, which employs the use of quantitative or qualitative feed restriction. During growing phase 468 White Leghorn (WLH) birds from random bred control population housed on deep litter housing system were exposed to three feeding regimes viz. T1 (ad lib.), T2 (Skip-two-days a week) and T3 (75% of ad lib.) on three different stocking densities viz. S1 (2.5 ft2/bird; 20 birds/pen), S2(2.0 ft2/bird; 25 birds/pen) and S3 (1.5 ft2/bird; 33 birds/pen) to form nine combinations of feed regimes and stocking density. Between 20 to 32 weeks of age, T1, T2 and T3 birds gained 31.76, 45.19 and 70.82 percent of body weight. The T1xS3 birds were heavier (1904.5±39.9 g) than other groups at the end of laying phase. The maximum feed consumed by T1 group (117.91±4.17 g) followed by T3 (116.61±3.80g) and T2 group (108.28±3.61 g), which differed significantly. T1xS3 birds consumed daily about 102 g feed and was significantly lower from other interaction groups. The birds kept under T3xS1 treatment gave maximum hen day egg production (64.36±6.78%) followed by T1xS2 (63.83±0.28%) and T1xS1 (61.71±4.84%). Hen housed egg production followed almost the same pattern with hen day egg production. Skip-two-days a week and 1.5-ft2/ bird treatment (T2xS3) produced eggs of 54.52 ±1.24 g weights, which were acceptable in market. It appears that skip-two-days fed birds reared on the density of 1.5 ft2/bird to be the most promising interaction group with respect to lower feed consumption during the laying period without any significant adverse effect on hen housed egg production. It appears that skip-two-days fed birds reared at the density of 1.5 ft2/bird to be the most promising interaction group with respect to lower feed consumption during the laying period.